Pengembangan Karakter Siswa dengan Permainan Bikabepo dan Wabidaka di SD Negeri Pucangan 03 Kecamatan Kartasura - ALI MA'SHUM FUADI (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
This innovative work on Student Character Development with Bikabepo and Wabidaka Games at SD Negeri Pucangan 03, Kartasura District, Sukoharjo Regency aims to describe the procedures for developing student character with Bikabepo and Wabidaka games at SD Negeri Pucangan 03Kartasura District, Sukoharjo Regency. Bikabepo is an acronym for Power Point Based Character Bus and Wabidaka is an acronym for Wayang Bus from Cardboard. Bikabepo and Wabidaka games were chosen as learning media to solve learning problems, namely to increase students' creativity and character development. The method used is the Research and Development (R and D) research method. The results of the implementation of this innovative work show that the use of Bikabepo and Wabidaka game media can develop student character and improve learning outcomes and student creativity in learning. The development of student character can be seen from the results of interviews with class teachers and guardians which show that 90% of students have been honest, disciplined and responsible in daily life. The learning outcomes showed an increase in learning completeness by 47%, which was originally by 30% after using Bikbepo and Wabidaka game media to 77%. In addition, student creativity also increases in learning based on the results of student work in making character buses and solving problems about character. 100% of students can answer questions about character issues in everyday life. Based on this, it can be concluded that powerpoint-based character bus games and cardboard bus puppets can develop the character, learning outcomes and creativity of students at SD Negeri Pucangan 03. Keywords: Character development, game, Bikabepo, Wabidaka